PENGARUH INVESTASI SWASTA DAN TENAGA KERJA TERHADAP PRODUK DOMESTIK REGIONAL BRUTO KOTA SAMARINDA - Titin Suprihatin (Jurnal Ilmu Ekonomi Mulawarman (JIEM), 2016)
The influence of Private Investment and Employment On the Gross Regional Domestic Product in Samarinda (under the guidance of Mr. Michael and Mr. Agus Junaidi).The purpose of this research is to determine the influence ofprivate invesment and as well as affects the dominant influence variable to Gross Domestic Product in the city of Samarinda.The hypothesis put forward in this research that is a, private investment and as well as private investment affects the dominant influence on the Gross Regional Domestic Product in Samarinda.The data used in this analysis is secondary data obtained from the Central Statistics Agency (BPS) is then calculated using a Cobb-Douglas.Analysis and processed using SPSS (Stastical Programme For Science) version 23.Based on the results obtained by simultaneous testing of private investment, and labor positive and significant impact on the Gross Domestic Product in Samarinda. While partially for private investment obtained by t = 1,876 significance and Labor force obtained t count = 13,849 with 0.000 significance. So based on these results we can conclude labor dominant influence on the Gross Domestic Product in Samarinda.Keywords: Private Investment, Labor, Gross Regional Domestic Produc